2004
DOI: 10.1021/bi0356653
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Cofactor Composition of Escherichia coli Biotin Synthase

Abstract: The cofactor content of in vivo, as-isolated, and reconstituted forms of recombinant Escherichia coli biotin synthase (BioB) has been investigated using the combination of UV-visible absorption, resonance Raman, and Mössbauer spectroscopies along with parallel analytical and activity assays. In contrast to the recent report that E. coli BioB is a pyridoxal phosphate (PLP)-dependent enzyme with intrinsic cysteine desulfurase activity (Ollagnier-deChoudens, S., Mulliez, E., Hewitson, K. S., and Fontecave, M. (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
100
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(107 citation statements)
references
References 48 publications
7
100
0
Order By: Relevance
“…3B), which comprises weak bands at 255, 365, and 390 cm Ϫ1 and an intense band at 338 cm Ϫ1 . The latter band is attributed to the symmetric breathing mode of the Fe 4 S 4 cubane, and the spectrum is very similar to those reported for [4Fe-4S] 2ϩ clusters in AdoMet-dependent radical enzymes (39,41,42 2ϩ clusters in the RR spectrum of the anaerobically prepared sample is likely to be a consequence, in whole or in part, of freezing and thawing of FIG. 3.…”
Section: Effect Of Isc and Suf Proteins As Well As The Groes/el Chapesupporting
confidence: 80%
See 1 more Smart Citation
“…3B), which comprises weak bands at 255, 365, and 390 cm Ϫ1 and an intense band at 338 cm Ϫ1 . The latter band is attributed to the symmetric breathing mode of the Fe 4 S 4 cubane, and the spectrum is very similar to those reported for [4Fe-4S] 2ϩ clusters in AdoMet-dependent radical enzymes (39,41,42 2ϩ clusters in the RR spectrum of the anaerobically prepared sample is likely to be a consequence, in whole or in part, of freezing and thawing of FIG. 3.…”
Section: Effect Of Isc and Suf Proteins As Well As The Groes/el Chapesupporting
confidence: 80%
“…2A) 2ϩ clusters in other members of the AdoMetdependent radical enzymes, e.g. anaerobic ribonucleotide reductase-activating enzyme (40), pyruvate formate-lyase-activating enzyme (41), biotin synthase (42), and the tRNA-methylthiotransferase MiaB (39). EPR studies only showed a near isotropic S ϭ 1/2 resonance centered near g ϭ 2.01 ( (46), and this was further supported by VTVH MCD saturation magnetization data, which cannot be fit based solely on an S ϭ 1/2 ground state and indicate the presence of Kramers' S Ͼ 1/2 component (Fig.…”
Section: Effect Of Isc and Suf Proteins As Well As The Groes/el Chapementioning
confidence: 99%
“…This instability enables the protein to complete the conformational change, initiated in step 1, which rearranges the cysteine ligands to accommodate the [2Fe-2S] 2ϩ cluster. We note that a mechanism similar to that described here for FNR may occur in the oxygen-induced degradation of the [4Fe-4S] 2ϩ cluster of biotin synthase and other radical SAM enzymes, which degrade to a semistable [2Fe-2S] 2ϩ cluster (40,41).…”
Section: [1]supporting
confidence: 53%
“…The enzyme is a homodimeric iron-sulfur protein in which each monomer contains both a [4Fe-4S] 2+ cluster and a [2Fe-2S] 2+ cluster [2]. The [4Fe-4S] 2+/+ cluster is bound to a conserved CxxxCxxC motif that is common to a large superfamily of AdoMet-dependent radical enzymes, while the [2Fe-2S] 2+ cluster, found only in BioB, is bound to 3 cysteines and an arginine that are located throughout the primary sequence [3][4][5]. The structure of E. coli BioB [6] shows that AdoMet is covalently coordinated to a unique iron in the catalytic [4Fe-4S] 2+ cluster, and both are bound to an extended loop at the C-terminal end of an (αβ) 8 barrel, with the [4Fe-4S] 2+ cluster ∼5-7 Å from the exterior of the protein.…”
Section: Introductionmentioning
confidence: 99%
“…They find that each BioB polypeptide chain produces, on average, ∼20 biotin molecules in 4 hrs (k cat ≈ 0.08 min -1 ), which therefore requires that active BioB is regenerated after each turnover. Since turnover is accompanied by loss of the [2Fe-2S] 2+ cluster, and possibly also the [4Fe-4S] 2+ cluster, and recent studies have demonstrated that BioB is inactive in the absence of these clusters [3,9,16], reactivation of the enzyme likely involves cluster repair or reassembly. In vivo, this process is may be mediated by the iron-sulfur cluster assembly systems (isc and/or suf operons in E. coli).…”
Section: Introductionmentioning
confidence: 99%